31. SURVEY ON PARENTS' KNOWLEDGE OF PREVENTION AND CONTROL OF HAND, FOOT AND MOUTH DISEASE AT HOA MI KINDERGARTEN, CHAU THANH DISTRICT HAU GIANG PROVINCE IN 2024 (Vietnam Journal of Community Medicine, 2025)
Hand, foot and mouth disease is an acute viral infection, with no specific treatment and no preventive vaccine. Mothers' knowledge about hand, foot and mouth disease is identified as playing a particularly important role in disease prevention for children. Objective: To determine the correct knowledge about prevention and control of hand, foot and mouth disease of parents at Hoa Mi Kindergarten, Chau Thanh district, Hau Giang province in 2024. Research subjects and methods:Cross-sectional study on 420 parents at Hoa Mi Kindergarten in Chau Thanh district, Hau Giang province in 2024. The survey form was built based on the document guiding the care of children with hand, foot and mouth disease. Results: 79.3% of parents of students know that contact with the nasal secretions of sick people will cause hand, foot and mouth disease and 68.1% of parents of students know that children under 5 years old are susceptible to hand, foot and mouth disease, know that hand, foot and mouth disease has symptoms of fever and blisters are 84.7% and 84.5% And 62.7% wash their hands before taking care of children to prevent hand, foot and mouth disease. Conclusion: Knowledge about prevention of hand, foot and mouth disease of parents of students is still lacking, health education and counseling programs are needed to improve knowledge for parents.
Keywords: Knowledge of prevention of hand, foot and mouth disease.